REPRESENTASI NAMA DIRI DALAM PEMILIHAN REKTOR UNIVERSITAS GADJAH MADA 2012: SEBUAH KAJIAN SEMIOTIK - Abdul Hakim (MABASAN, 2017)
This research aims to explain the relation of self-names and position who are accupy in the election of rector candidates’ period 2012--2017. This research was conducted using Perice theory with interpretation method which consider that sign is recognized as sign only if being interpreted as sign. The name of candidate is interpreted to overview its relation with the voting result in winning the election. The practice in becoming the elected rector with the most votes is participated by Marsudi Triatmojo and Danang Parikesit. The voting winner of Pratikno is a form of representation of self-name which is being interpreted as sign with type or characteristic of sign which has meaning for to do or to act, Marsudi Triamojo with the characteristic of sign which is interpreted as willingness concept, while Danang Parikesit is a sign which is interpreted as accompany charcteristic. Hence, self-name was constructed social practice in election.